2020
DOI: 10.4149/km_2020_5_341
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical and wear behaviour of graphene reinforced aluminium alloy 6061 metal matrix composite

Abstract: Owing to its outstanding mechanical and thermal properties, graphene has shown enormous potentials as an improvement material for composites. This paper investigates the properties of graphene-reinforced 6061 aluminium alloy Metal Matrix Composites (MMCs) with varying weight percentages (5 and 10 wt.% graphene) of reinforcement. Energy Dispersive Spectroscopy (EDS) and Scanning Electron Microscope (SEM) studies of the MMC confirm the presence and distribution of graphene particles in the Al6061 matrix material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Lin et al [17] explored the synergistic effect of TiN-Ag coating and MLG-rich grease to improve the friction, wear, and conduction of copper connectors. Jabith et al [18] and Sendhil Kumer et al [19] studied copper matrix composites and aluminium matrix composites with added graphene, respectively. Their results showed that the presence of graphene enhanced the tribological behaviour while increasing the hybrid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [17] explored the synergistic effect of TiN-Ag coating and MLG-rich grease to improve the friction, wear, and conduction of copper connectors. Jabith et al [18] and Sendhil Kumer et al [19] studied copper matrix composites and aluminium matrix composites with added graphene, respectively. Their results showed that the presence of graphene enhanced the tribological behaviour while increasing the hybrid composition.…”
Section: Introductionmentioning
confidence: 99%